ONOMATOPOEIA ANALYSIS IN THE GOD OF HIGH SCHOOL WEBTOON COMIC - Wijaya, I Kadek Yoga; Candra, Komang Dian Puspita; Juniartha, I Wayan (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThe goal of this research is to find out the occurrence of onomatopoeia in the webtoon comicentitled The God of High School. People nowadays like reading comic books as a form of pleasure.Comic books are currently available in both hardcopy and digital formats, particularly over theinternet. The God of High School is a popular web comic among teenagers. Onomatopoeia refersto the use of words in comic books to reflect the noises and motions that occur in the panels. Theuse of an onomatopoeia word in a comic is significant because, unlike novels, comics have alimited amount of space in which to explain a scenario with a large number of phrases. This studywas analysed qualitatively by using theory from Bredin (1996) about the types of onomatopoeiaand theory from Thomas (1995) about the meaning. The findings of this study show that all typesof of onomatopoeia words occurred in the webtoon comic entitled The God of High School.Exemplary onomatopoeia is found more frequently than the other two forms, including 41 directonomatopoeia, 8 associative onomatopoeia, and 76 exemplary onomatopoeias. The total numberof words in the data is 125.Keywords: Onomatopoeia, linguistic, webcomicABSTRAKPenelitian ini bertujuan untuk menemukan kemunculan onomatopoeia dalam komik webtoon TheGod of High School. Orang-orang saat ini suka membaca buku komik sebagai bentuk kesenangan.Buku komik saat ini tersedia dalam format hardcopy dan digital, terutama melalui internet. TheGod of High School adalah webcomic yang populer di kalangan remaja. Onomatopoeia mengacupada penggunaan kata-kata dalam buku komik untuk mencerminkan suara dan gerakan yangterjadi di panel. Penggunaan kata onomatopoeia dalam komik sangat penting karena, tidak sepertinovel, komik memiliki ruang terbatas untuk menjelaskan skenario dengan sejumlah besar frasa.Penelitian ini dianalisis secara kualitatif menggunakan Theory dari Bredin (1996) tentang tipe darionomatopoeia dan untuk menganalisis maknanya menggunakna teori dari Thomas (1995).Berdasarkan hasil analisis, semua jenia onomatopoeia ditemukan dalam komik webtoon berjudulThe God of High School. Tipe exemplary onomatopoeia ditemukan lebih sering daripada duabentuk lainnya, antara lain 41 direct onomatopoeia, 8 associative onomatopoeia, dan 76 exemplaryonomatopoeia. Jumlah kata yang mengandung onomatopoeia dalam data adalah 125.Kata kunci: Onomatopoeia, linguistik, komik web